E-anfun detects odour volatility in industry, UMP and SDR find solution due to pollution - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PAYA BESAR, 11 January 2022 - The collaboration between researchers from Universiti Malaysia Pahang (UMP) and Sime Darby Plantation Research (SDPR) in the project The Development of Odor Sensor to Monitor The Soybean Extraction Plant for Odor Mitigation Project via an MTUN matching grant successfully detected the source of odour pollution at the soy oil extraction plant (Sime Darby Oil) located in a local community in Nonthaburi, Thailand.